(untitled) (Світ фінансів, 2017)
Мацієвич Т. О. Теоретичні засади фінансового механізму та його роль у забезпеченні екологічної політики. Розкрито сутність, завдання та призначення екологічної політики. Розглянуто теоретичні аспекти функціонування механізму фінансового забезпечення реалізації екологічної політики в Україні. Систематизовано основні складові фінансового механізму у фінансовому забезпеченні і фінансовому регулюванні реалізації екологічної політики. Узагальнено основні дефініції категорії “фінансовий механізм”. Доповнено перелік елементів фінансового механізму реалізації екологічної політики. Проаналізовано теоретично-методологічні підходи до визначення терміна “фінансовий механізм екологічної політики”. Мациевич Т. А. Теоретические основы финансового механизма и его роль в обеспечении экологической политики. Раскрыты сущность, задачи и назначения экологической политики. Рассмотрены теоретические аспекты функционирования механизма финансового обеспечения реализации экологической политики в Украине. Систематизированы основные составляющие финансового механизма в финансовом обеспечении и финансовом регулировании реализации экологической политики. Обобщены основные дефиниции категории “финансовый механизм”. Дополнен перечень элементов финансового механизма реализации экологической политики. Проанализированы теоретико-методологические подходы к определению термина “финансовый механизм экологической политики”. Matsijevych T. Theoretical foundations financial mechanism and its role in promoting environmental policy. The course of Ukraine to improve the financial autonomy of local governments actualised problems of theoretical and practical nature relating to the financial aspects of the implementation of environmental policies on the ground, with financial sources to ensure a continuous process of restoring natural resources of solving environmental problems. Purpose is requires a deep research and study the order of formation and functioning of the financial mechanism at the grassroots levels of government. Formed on the basis of the applicable environmental, tax and budget legislation financial mechanism for the implementation of environmental policy, involves collecting appropriate payments for natural resources, environmental pollution and environmental activities financing system is not effective. The system of environmental management is too centralized, thus reducing the efficiency of management at the regional level and makes it impossible to take full account of territorial interests in creating environmentally safe environment. Research principles of the functioning mechanism of financial support the implementation of environmental policy in Ukraine made it possible to determine its theoretical and methodological and practical principles clarify the status and key problems, propose solutions. Therefore, a prerequisite for the formation of conceptual strategies of economic activities in the field of ecology should be the introduction of the financial mechanism, the essence of which is the formation of a purely economic relations in the use of natural resources, promotion of sustainable and integrated use and reproduction. Out of this situation is possible in terms of simultaneous formation and implementation of the conceptual foundations of ecological development at national and regional levels from the perspectives of national regional policy and strengthening regional autonomy, creating favorable conditions for their self-development.